IMPLEMENTATION OF UMMI METHOD: LEARNING QUR’AN FOR THE ELDERLY - Multihakiki, Munfiq Rosandi; El-Yunusi, Muhammad Yusron Maulana (Universitas Labuhanbatu, 2024)
TThis study explores the application of the Ummi method for teaching the Qur'an to elderly learners at the Fastabiqul Khairat Qur'an House in Landasan Ulin District, Banjarbaru City. It addresses a key issue: the tendency for elderly participants to laugh when making mistakes during lessons, which can affect their learning experience. The research aims to understand how the Ummi method is implemented in this context, as well as the factors that facilitate or impede the learning process for elderly individuals. Utilizing a qualitative field research approach, the study involves interviews and observations with a Qur'an teacher, focusing on the experiences of elderly learners using the Ummi method. Data analysis includes reduction, presentation, and verification to draw meaningful conclusions. The study of the application of the Ummi Method at Rumah Qur’an Fastabiqul Khairat for elderly learners reveals that, overall, the method is effective in improving Quranic learning, especially in the memorization of short surahs and the application of Tajweed. Key factors contributing to this success include the educational background and teaching experience of Ustadzah Nur Hafizah, the structured approach to lesson planning, and the high motivation and enthusiasm of the elderly participants. These factors create a conducive learning environment that supports the objectives of the Ummi Method. However, challenges such as memory retention difficulties and the varied sensitivities of elderly learners present notable obstacles. To overcome these, tailored approaches, including more frequent repetition and an empathetic teaching style, are crucial in helping elderly learners achieve better outcomes.